Demand for credit in Ecuador: which workers most urgently need a credit to reactivate their economy in the context of the COVID-19 health crisis? - Uquillas, Adriana (2022)
COVID-19 brought with it an increase in unemployment, underemployment and workers living in poverty. Epidemics and economic crises may have a disproportionate impact on certain population groups and lead to increased inequality. To design public policies that reactivate the economy from the point of view of financial accessibility, it is necessary to identify this population in a situation of fragility. Based on a survey conducted at the national level, this study establishes the profiles of the most vulnerable workers and the socio-demographic and economic characteristics that determine the demand for credit in the most fragile labor sectors of Ecuador in the COVID-19 crisis.The results show that the main determinants are not owning savings, not owning a home, owning debts, and decreasing income. Professionals dedicated to teaching and self-employed or belonging to EPS organizations that operate mainly in the retail trade or other service activities correspond to this vulnerable group.It is essential to strengthen social protection systems, design financial instruments to support those who need it most through the creation and diversification of special credit lines adjusted to different vulnerability profiles.